Catalysing governance transformations through urban resilience implementation: The case of Thessaloniki, Greece. (December 2020) - Pitidis, Vangelis; Coaffee, Jon
Highlights: The implementation of resilience strategies can induce governance transformations. Case studies of resilience implementation can provide invaluable insights for resilience theory and practice. Mainstreaming urban resilience is a time-consuming and resource intensive process. Working across silos is key in mobilising the adaptive governance capacity. Political determination and a common vision are key to avoiding implementation gaps.